2015
DOI: 10.5897/ajbm2014.7623
|View full text |Cite
|
Sign up to set email alerts
|

The relation between organizational trust, organizational support and organizational commitment

Abstract: Organizations are bodies composed of people who gather in order to reach specific objectives. This situation prompts the organizations to produce people oriented policies and increase the interest in the subject of organizational commitment. However, there are not much academic studies in Turkey on organizational commitment. The general objective of this research was to assess the relationship between organizational trust, organizational support and organizational commitment of administrators/teachers. The par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 14 publications
0
11
0
2
Order By: Relevance
“…Izgar (2000) found a meaningful relationship between the branch of the teachers and emotional exhaustion. In the study, Eğriboyun (2013) found that there was no meaningful difference in perceptions of organizational commitment, emotional commitment, continuity and normative commitment in the study. (Tuğrul, B and Çelik, E. 2002;Gündüz, 2004).…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Izgar (2000) found a meaningful relationship between the branch of the teachers and emotional exhaustion. In the study, Eğriboyun (2013) found that there was no meaningful difference in perceptions of organizational commitment, emotional commitment, continuity and normative commitment in the study. (Tuğrul, B and Çelik, E. 2002;Gündüz, 2004).…”
Section: Discussionmentioning
confidence: 76%
“…It has been found that teachers who work in private schools experience less emotional exhaustion and desensitization than teachers who work in public schools and experience more personal success (Korkmaz, 2004). Eğriboyun (2013) according to school type; it was found that exhaustion levels of teachers working in state school Karacan (2012) are over the averages in all sub-dimensions, indicating that there is a meaningful relationship between perceptions of organizational commitment and normative commitment. It can be said that the motivations of the teachers working in the private school are at a high level because of the loss of work.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Yıl-maz (2008), ilkokul öğretmenleri üzerine yaptığı araştırmada, öğretmen-lerin örgütsel güven algıları arttıkça duygusal örgütsel bağlılıklarının orta düzeyde arttığını ortaya koymaktadır. Eğriboyun (2015), ortaokul öğret-menlerinin örgütsel güven algıları ile duygusal örgütsel bağlılıkları arasında orta düzeyde pozitif yönde anlamlı bir ilişki olduğunu belirtmektedir. Özgan (2011) ise liselerde görevli öğretmenlerin örgütsel güven algı-ları ile öğretmenlerin örgütsel bağlılıkları arasında pozitif ve orta düzeyde bir ilişki olduğunu ve öğretmenlerin örgütsel güven algılarının örgütsel bağlılığı yordadığını kanıtlamaktadır.…”
Section: öRgütsel Güven Ile Duygusal Bağlılıkunclassified